2013
DOI: 10.1111/fwb.12142
|View full text |Cite
|
Sign up to set email alerts
|

Elevated light and nutrients alter the nutritional quality of stream periphyton

Abstract: Summary The biochemical composition of primary food resources may affect secondary production, growth, reproduction and other physiological responses in consumers and may be an important driver of food‐web dynamics. Changes in land use, riparian clearing and non‐point nutrient inputs to streams have the potential to alter the biochemical composition of periphyton, and characterising this relationship may be critical to understand the processes by which environmental change can affect food webs and ecosystem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
52
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 54 publications
2
52
0
2
Order By: Relevance
“…These findings might be related to physiological responses of periphyton to differences in nutrient concentrations. Some studies have reported that added nutrients lead to an increase in the proportions of ALA in periphyton (Cashman, Wehr, & Truhn, 2013;Guo et al, 2016;Hill et al, 2011), but unfortunately we did not analyse periphyton fatty acids in this study. In phytoplankton, low nutrient concentrations lead to the production of PUFA-poor triacylglycerols, whereas high nutrient concentrations lead to an increase of PUFA-rich galactolipids in the algae (Guschina & Harwood, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…These findings might be related to physiological responses of periphyton to differences in nutrient concentrations. Some studies have reported that added nutrients lead to an increase in the proportions of ALA in periphyton (Cashman, Wehr, & Truhn, 2013;Guo et al, 2016;Hill et al, 2011), but unfortunately we did not analyse periphyton fatty acids in this study. In phytoplankton, low nutrient concentrations lead to the production of PUFA-poor triacylglycerols, whereas high nutrient concentrations lead to an increase of PUFA-rich galactolipids in the algae (Guschina & Harwood, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…The LC‐PUFA content of periphyton is sensitive to seasonal and spatial variation in stream environmental conditions (Hill et al ; Cashman et al ; Guo et al ). For example, the extent of FA unsaturation in algae can vary with temperature.…”
mentioning
confidence: 99%
“…Although not correlated with nutrients in our study, increases in proportions of Σω3 FAs and EPA in periphyton could have been associated with increased nutrients in more urban catchments, given their well‐documented mechanistic links to increased FA production (Dalu, Galloway, Richoux, & Froneman, ; Guo et al., ; Whorley & Wehr, ), although high levels of nutrients also can lead to reduced proportions of ≥20‐C FAs in algae (Cashman et al., ). Within agricultural systems, biofilms contained greater concentrations of important FA compounds as nutrient availability increased, despite exhibiting decreased taxonomic diversity and more eutrophic indicative taxa (Whorley & Wehr, , ).…”
Section: Discussionmentioning
confidence: 55%
“…The strong correlations of Σω3 FAs and EPA proportions with chloride concentrations could indicate nutrient effects as well, because chloride is a conservative tracer of water delivered to streams from sources affected by human activities, and is less affected than nutrients by biological uptake and transformation. Canopy cover by riparian trees, which was qualitatively abundant at most sites, may have further promoted higher proportions of periphyton EPA and ω3 FAs by reducing oxidative damage to their carbon double bonds and by reducing the amount of surplus carbon stored as saturated, monounsaturated, and shorter 18‐C FAs under high light conditions (Cashman et al., ; Hill et al., ; Twining et al., ).…”
Section: Discussionmentioning
confidence: 99%